Prediction models for scour depth around circular compound bridge piers - Siva Krishna Reddy; Venu Chandra (Water Science and Engineering)
Scour around bridge pier foundations is a complex phenomenon that can threaten structural stability. Accurate prediction of scour depth around compound piers remains challenging for bridge engineers. This study investigated the effect of foundation elevation on scour around compound piers and developed reliable scour depth prediction models for economical foundation design. Experiments were conducted under clear-water conditions using two circular piers: (1) a uniform pier (with a diameter of D) and (2) a compound pier consisting of a uniform pier resting on a circular foundation (with a foundation diameter (Df) of 2D) positioned at various elevations (Z) relative to the channel bed. Results showed that foundation elevation significantly affected scour depth. Foundations at or below the bed (Z/D ≥ 0) reduced scour, while those projecting into the flow field (Z/D < 0) increased scour. The optimal foundation elevation was found to be 0.1D below the bed level, yielding a 57% reduction in scour depth compared to the uniform pier due to its shielding effect against downflow and horseshoe vortices. In addition, regression, artificial neural network (ANN), and M5 model tree models were developed using experimental data from this and previous studies. The M5 model outperformed the traditional HEC-18 equation, regression, and ANN models, with a coefficient of determination greater than 0.85. Sensitivity analysis indicated that flow depth, foundation elevation, and diameter significantly influenced scour depth prediction, whereas sediment size had a lesser impact.